Effect of integrated traditional Chinese medicine and western medicine on the treatment of severe acute respiratory syndrome: A meta-analysis - Chen Y; Guo JJ; Healy DP; Zhan S (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Background: Data regarding the treatment efficacy of integrative treatment of Traditional Chinese Medicine (TCM) and Western Medicine (WM) in treating patients with (SARS) are conflicting. The effects of integrative TCM/WM treatment have not been fully quantified. Objectives: To systematically asses the treatment effects of integrated TCM with WM versus WM alone in patients with SARS, incorporating data from recently published studies. Methods: A meta-analysis was conducted, using published randomized and nonrandomized controlled clinical studies that compared the treatment effects of integrative TCM/WM with WM alone from 2002 to 2006.The outcome measurements included mortality rate, cure rate, resolution of pulmonary infiltrate, use of corticosteroid, and time to defervescence. The effect sizes were presented as risk ratio (RR), rate difference (RD), and weighted mean difference (WMD).The pooled effect sizes were calculated by both fixed-effects and random-effects models. Results: A total of 1,678 patients with a diagnosis of SARS were identified, including 866 patients from 16 randomized controlled studies and 812 patients from 8 nonrandomized controlled studies. There were no differences detected in mortality rate or cure rate between treatments. Compared with patients receiving WM treatment alone, patients receiving integrative treatment were more likely to have complete or partial resolution of pulmonary infiltrate (RD=0.18, 95%CI; 0.07 to 0.30), lower average daily dosage (mg) of corticosteroid (WMD=-60.27, 95% CI; -70.58 to -49.96), higher CD4+ counts (cells/uL) (WMD=167.96, 95% CI; 109.68 to 226.24), and shorter time to defervescence (days) (WMD= -1.06, 95%CI;-1.60 to -0.53).Conclusions: The experience of integrative TCM/WM in the treatment of SARS is encouraging. The use of TCM as an adjunctive therapy in the treatment of SARS should be further investigated.